PENGARUH PENGGUNAAN PAPAN MISTERI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V UPTD SD NEGERI 125549 PEMATANGSIANTAR - Sonima Situngkir; Yanti Arasi Sidabutar; Melvin M. Simanjuntak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the Effect of the Use of Mystery Boards on Student Learning Outcomes in the Indonesian Language Subject of Class V UPTD SD Negeri 125549 Pematangsiantar. There are 2 hypotheses in this study, namely: (Ha) there is an Effect of the Use of Mystery Boards on Student Learning Outcomes in the Indonesian Language Subject of Class V UPTD SD Negeri 125549 Pematangsiantar. (Ho) there is no Effect of the Use of Mystery Boards on Student Learning Outcomes in the Indonesian Language Subject of Class V UPTD SD Negeri 125549 Pematangsiantar. This research was conducted in the 2024/2025 academic year in April. This research method is an experiment with a pre-experimental design research type with a One-Group Pretest-Posttest Design research design. The sample of this study consisted of 25 students. The data collection techniques used were tests, documentation, and observation. The data was processed using statistical analysis techniques of normality tests and t-tests. Based on the results of the hypothesis test, the calculated t is = 21.00 and the t table value = 2.064 with a significance level of 0.05, because the significant probability is 0.000 <0.05 or the calculated t value> t table and the results obtained t count = 21.00> t table = 2.604 then HO is rejected and Ha is accepted there is The Effect of Using Mystery Boards on Student Learning Outcomes in Indonesian Language Subjects Class V UPTD SD Negeri 125549 Pematangsiantar.